Investigative journalism - Burgh, Hugo de; Bradshaw, Paul (London Routledge, 2021)
"This 3rd edition maps the new world of Investigative Journalism, where technology and globalisation have connected and energized journalists, whistle-blowers and the latest players, with far-reaching consequences in politics and business worldwide. In this new edition, expert contributors demonstrate how crowdsourcing, big data, globalization of information and changes in media ownership and funding have escalated the impact of investigative journalists. The book includes case studies of investigative journalism from around the world including the exposure of EU corruption, destruction of the Malaysian environment, and investigations in China, Poland and Turkey. From Ibero-America to Nigeria, India to the Arab world, investigative journalists intensify their countries' evolution by inquisition and revelation. This new edition reveals how investigative journalism has gone digital and global. Investigative Journalism is essential for all those intending to master global politics, international relations, media and justice in the 21st century"--
Includes bibliographical references and index.
Keywords: Investigative reporting; Journalism